Middle atmospheric oscillation over India and its possible association with Indian summer monsoon - MUKHOPADHYAY, R. K.; SARKAR, T. K. (MAUSAM, 1990)
In this paper the middle atmospheric oscillations of the zonal wind in upper stratosphere and lower mesosphere have been analysed and studied using the rocket sonde wind data of Thumba and Balasore It was observed that in the mean, picture, t e semi-annual oscillation at on was predominant in the equatorial Indian region (i, e.,over Thumba ) while the annual wave was predominant over tropical Indian region (i.e over Balasore), During good monsoon year, a strong semi-annual wave over tropical Indian region was observed . The amplitude of this semi-annual wave was also found to be significantly higher over the equatorial Indian region during good monsoon year, The study seem3 to reveal a close association of the middle atmospheric oscillations over India with the summer monsoon.